PENGARUH LIKUIDITAS, LEVERAGE, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABLITAS PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Nur Safitri; Hetty Muniroh (Jurnal Bina Akuntansi, 2023)
The purpose of this study was to determine the effect of liquidity, leverage, capital structure and company size on profitability. This study used a purposive sampling technique in taking the sample, so that a sample of 24 LQ45 companies were registered on the IDX in 2019-2021. Methodssof data collectionnusing theemethod of documentation. The data analysis technique uses multiple linear regression analysis using SPSS version 19. The results of this study indicate that liquidity has no significant negative effect onNprofitability. Leverageehas a significant negative effect on profitability. Meanwhile, capital structure and firm size have no significant positiveeeffect onnprofitability.